Experimental Study and Mathematical Modeling of Thin-Layer Infrared Drying of Watermelon Seeds - Doymaz, Ibrahim (WILEY, 2014)
The effect of different infrared power levels on drying kinetics of watermelon seed was investigated. The seeds dried at 83, 125, 167 and 209W infrared powers. It was observed that the power level affected the drying and rehydration characteristics of watermelon seeds. Drying time reduced from 170to 40min as the infrared power level increased from 83 to 209W. Midilli etal. and Hii etal. models are satisfactorily described drying kinetics. Effective diffusivity varied from 0.72x10-10 to 3.78x10-10m2/s and activation energy was calculated as 15.45kW/kg. The highest energy efficiency was found for the samples dried at 209W. Practical Applications Watermelon is an important crop grown in the warmer regions of the world. The fresh or juice from watermelon is used for human consumption. It contains large quantities of seeds, which can be cooked, dried and served as snacks. Because of high initial moisture content, the watermelon seed is very sensitive to microbial spoilage. Drying is one of the preservation methods applied to agricultural products. The basic objective of drying agricultural products is the removal of water in the solids up to a certain level, at which microbial spoilage and deterioration chemical reaction are greatly minimized. Besides, knowledge of drying characteristics is important in the design, simulation and optimization of drying process.
Keywords: MOISTURE DIFFUSIVITY; KINETICS; RADIATION; SLICES; OPTIMIZATION; KERNELS; Food Science & Technology